2016
DOI: 10.1037/xhp0000205
|View full text |Cite
|
Sign up to set email alerts
|

Not quite so blind: Semantic processing despite inattentional blindness.

Abstract: We often fail to detect clearly visible, yet unexpected objects when our attention is otherwise engaged, a phenomenon widely known as inattentional blindness. The potentially devastating consequences and the mediators of such failures of awareness have been studied extensively. Surprisingly, however, hardly anything is known about whether and how we process the objects that go unnoticed during inattentional blindness. In 2 experiments, we demonstrate that the meaning of objects undetected due to inattentional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 25 publications
6
49
1
Order By: Relevance
“…Summarizing, high-level cognitive processing that requires the integration of lower-level stimulus features seems to be diminished when stimuli are fully task-irrelevant, contrary to previous findings of perceptual processing outside the scope of attention (Peelen et al, 2009;Sand & Wiens, 2011;Schnuerch et al, 2016;Tusche, Kahnt, Wisniewski, & Haynes, 2013). These findings suggest crucial limitations of the brain's capacity to process task-irrelevant "complex" cognitive control-initiating stimuli, suggestive of an attentional bottleneck at high levels of information analysis.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…Summarizing, high-level cognitive processing that requires the integration of lower-level stimulus features seems to be diminished when stimuli are fully task-irrelevant, contrary to previous findings of perceptual processing outside the scope of attention (Peelen et al, 2009;Sand & Wiens, 2011;Schnuerch et al, 2016;Tusche, Kahnt, Wisniewski, & Haynes, 2013). These findings suggest crucial limitations of the brain's capacity to process task-irrelevant "complex" cognitive control-initiating stimuli, suggestive of an attentional bottleneck at high levels of information analysis.…”
Section: Resultscontrasting
confidence: 86%
“…It was long thought that only basic physical stimulus features or very salient stimuli are processed in the absence of attention (Treisman & Gelade, 1980), due to an "attentional bottleneck" at higher-levels of analysis (Broadbent, 1958;Deutsch & Deutsch, 1963;Lachter, Forster, & Ruthruff, 2004;Wolfe & Horowitz, 2004). However, it has been shown recently that several tasks may in fact still unfold in the (near) absence of attention, including perceptual integration (Fahrenfort, van Leeuwen, Olivers, & Hogendoorn, 2017), the processing of emotional valence (Sand & Wiens, 2011;Stefanics, Csukly, Komlósi, Czobor, & Czigler, 2012), semantical processing of written words (Schnuerch, Kreitz, Gibbons, & Memmert, 2016) and visual scene categorization (Fei-Fei, VanRullen, Koch, & Perona, 2002;Gronau & Izoutcheev, 2017;Peelen, Fei-Fei, & Kastner, 2009). Although one should be cautious in claiming complete absence of attention (Lachter et al, 2004), these and other studies have pushed the boundaries of potential processing without attention, and may even question the existence of an attentional bottleneck at all.…”
Section: Introductionmentioning
confidence: 99%
“…masked stimulus (the prime) can affect the perception of a subsequent stimulus (the target) has been taken as evidence that semantic processing can take place without awareness (e.g., Dehaene et al, 1998;Kiefer, 2002;Marcel, 1983) and even without attention (e.g., Luck, Vogel, & Shapiro, 1996;Maki, Frigen, & Paulson, 1997). More recently, Schnuerch, Kreitz, Gibbons, and Memmert (2016) showed that stimuli remaining unnoticed due to inattentional blindness nevertheless interfere with the processing of semantically-related attended objects, providing further evidence that the meaning of unconscious stimuli can be accessed instantaneously.…”
Section: Automaticity Of Semantic Processingmentioning
confidence: 99%
“…Also, imaging methods were able to demonstrate substantial neuronal marks of stimuli that remain beneath the threshold of awareness due to inattentional blindness (Pitts, Martínez, & Hillyard, 2012): Amplitudes of early eventrelated potentials (ERPs) that were recorded over the occipital pole differentiated between visually presented shapes and random arrays regardless of whether or not participants were aware of the shapes. Finally, there are even hints in inattentional blindness research indicating that the processing of objects that remain undetected goes beyond mere perceptual processing: A recent study provides direct evidence for the conclusion that the semantics of the undetected stimuli can be processed preconsciously; in two experiments, reaction times for target stimuli in a primary task were significantly slower when the semantic content of an undetected stimulus contradicted that of the attended, to-be-judged stimulus (Schnuerch, Kreitz, Gibbons, & Memmert. 2016; for indirect evidence see also Calvillo & Jackson, 2014;Koivisto & Revonsuo, 2009).…”
mentioning
confidence: 99%